THE ROLE OF CERTIFICATION AND EUROPEAN STANDARDSIN ENSURING THE COMPETITIVENESS OF UKRAINIAN ORGANIC PRODUCERS - ANDRUSENKO, Nadiia; PRUTSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Organic production in Ukraine is a pivotal area of development in the agricultural sector, ensuring the creation of high-value-added products and opening up significant opportunities for entering international markets. The development of this segment plays a crucial role in the implementation of environmentally sustainable practices in agriculture, the enhancement of food product quality, and the strengthening of Ukraine's position in the global organic production arena. Over the past decade, there has been a consistent growth in the area dedicated to organic production and the number of certified operators. This indicated a growing interest in organic farming methods and an increasing demand for environmentally friendly products in both domestic and foreign markets.However, the full-scale war that began in 2022 and the subsequent deepening of economic challenges have significantly impacted the industry, causing substantial disruptions in production and logistics chains. According to analytical research, the number of certified organic market operators in Ukraine decreased from 617 in 2021 to 544 in 2023, marking the lowest figure in the last five years. This reduction is a result of a complex interplay of external and internal factors, among which the loss of certified land due to occupation and hostilities, as well as the transformation of the production structure necessitated by the need to adapt to new realities, are particularly significant.The loss of control over significant agricultural lands, especially in the south and east of the country where substantial areas of organic production were traditionally concentrated, has led to a decrease in the total area of certified land and, consequently, to a reduction in the volume of organic product output. Furthermore, the destruction of infrastructure, the complication of logistical routes, and the mobilization of qualified personnel have also negatively affected the operations of organic farms.Despite the aforementioned difficulties, the European Union remains the primary export market for Ukrainian organic products. This underscores the importance of Ukrainian producers orienting themselves towards European quality and food safety standards. Ensuring compliance with the strict requirements of the EU and successfully undergoing the certification procedure are critical for maintaining the competitiveness of Ukrainian producers on a global scale and for the further development of the organic sector's export potential.Further growth and recovery of the organic sector in Ukraine will require comprehensive efforts from the state, businesses, and international partners. Support is needed for the restoration of production capacities, the attraction of investments, the simplification of certification procedures, and the provision of access to financing. Additionally, strengthening cooperation with European partners for the harmonization of legislation and the facilitation of trade relations is important. The development of the domestic market for organic products is also a crucial factor in ensuring the long-term stability of the industry. Raising consumer awareness about the benefits of organic products and supporting domestic producers will contribute to the growth of demand and the expansion of the internal market.Thus, organic production in Ukraine, despite the current challenges, retains its strategic potential for the sustainable development of agriculture, the improvement of nutrition quality, and the strengthening of the country's position in the international arena. Overcoming the consequences of the war and implementing systemic support measures will contribute to the recovery and further growth of this important segment of the economy.
Keywords: organic production; certification; European standards; competitiveness; international trade; export; added value; state support